The surgical strategy of hormonally active primary cardiac paraganglioma sarcoma: A case report - Wang, Xiangyu; Liu, Haiyuan; Zhang, Shuaipeng; Huang, Shaojun; Zhang, Chengxin (Frontiers in Cardiovascular Medicine, 2022)
Cardiac paraganglioma is a kind of rare neuroendocrine tumor characterized by the persistent secretion of catecholamines. Under excessive exposure of catecholamines, some atypical symptoms are presented, including hypertension, arrhythmias, and headache. The case of surgical treatment of a 28-year-old woman with primary cardiac paraganglioma is presented for experience sharing and surgical skill improvements.